A Set of Actions to Improve the General Cultural Standard of First Year Transfusion Medicine Students - Dinorah Pilar Betancourt González; Mercedes Diego Cobelo; José Zabala Cuesta (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2011)
Background: in order to face the challenges of the present century, universities require teachers and graduate students with a high cultural standard that validates the society model that is being built in Cuba. Objective: to propose a set of actions to improve the general cultural standard of Transfusion Medicine students at the Subsidiary of the Medical Sciences University of Cienfuegos. Method: The sample consisted of all first year Transfusion Medicine students. Theoretical and empirical methods were used. Results: The sources of information students used the most were reading and cinema. Weaknesses were found in the program in relation to the formation of a general cultural standard in future graduates. A first action proposed was to diagnose aspirations and cultural training needs of students. A second action will be to coordinate a project taking these needs into account. Next, an action will be dedicated to political, ideological and aesthetic aspects as well as to communication skills of teachers for the implementation of the project. Finally, evaluation will be conducted. Conclusion: These results show the need of further training in order to achieve a high cultural standard in Transfusion Medicine students.